Neuropeptide Y1 and alpha‐1 adrenergic receptor‐mediated decreases in functional vasodilation in gluteus maximus microvascular networks of prediabetic mice. Issue 13 (6th July 2018) - Novielli‐Kuntz, Nicole M.; Lemaster, Kent A.; Frisbee, Jefferson C.; Jackson, Dwayne N.
Abstract: Prediabetes is associated with impaired contraction‐evoked dilation of skeletal muscle arterioles, which may be due to increased sympathetic activity accompanying this early stage of diabetes disease. Herein, we sought to determine whether blunted contraction‐evoked vasodilation resulted from enhanced sympathetic neuropeptide Y1 receptor (Y1R) and alpha‐1 adrenergic receptor ( α 1R) activation. Using intravital video microscopy, second‐, third‐, and fourth‐order (2A, 3A, and 4A) arteriolar diameters were measured before and following electrical field stimulation of the gluteus maximus muscle (GM) in prediabetic (PD, Pound Mouse) and control (CTRL, c57bl6, CTRL) mice. Baseline diameter was similar between groups; however, single tetanic contraction (100 Hz; 400 and 800 msec) and sustained rhythmic contraction (2 and 8 Hz, 30 sec) evoked rapid onset vasodilation and steady‐state vasodilatory responses that were blunted by 50% or greater in PD versus CTRL. Following Y1R and α 1R blockade with sympathetic antagonists BIBP3226 and prazosin, contraction‐evoked arteriolar dilation in PD was restored to levels observed in CTRL. Furthermore, arteriolar vasoconstrictor responses to NPY (10 −13 –10 −8 mol/L) and PE (10 −9 –10 −5 mol/L) were greater in PD versus CTRL at higher concentrations, especially at 3A and 4A. These findings suggest that contraction‐evoked vasodilation in PD is blunted by Y1R and α 1R receptor activation throughout skeletal muscle arteriolar networks. Abstract : Elevated activation of peptidergic and adrenergic receptors blunts arteriolar responses to muscle contraction in a murine model of prediabetes.